2019
DOI: 10.1002/mrm.27988
|View full text |Cite
|
Sign up to set email alerts
|

Cell penetrating peptide functionalized perfluorocarbon nanoemulsions for targeted cell labeling and enhanced fluorine‐19 MRI detection

Abstract: Purpose: A bottleneck in developing cell therapies for cancer is assaying cell biodistribution, persistence, and survival in vivo. Ex vivo cell labeling using perfluorocarbon (PFC) nanoemulsions, paired with 19 F MRI detection, is a noninvasive approach for cell product detection in vivo. Lymphocytes are small and weakly phagocytic limiting PFC labeling levels and MRI sensitivity. To boost labeling, we designed PFC nanoemulsion imaging probes displaying a cell-penetrating peptide, namely the transactivating tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 68 publications
0
79
0
Order By: Relevance
“…Oximetry Response to CAR T-cell Therapy against Glioma by 19 F MRI: A Murine Model An alternative PFC nanoemulsion formulation displayed a cell-penetrating peptide as a component of the surfactant to boost cell labeling in T cells and other weakly phagocytic cell types (21), namely, the transactivating transcription sequence (TAT) of the human immunodeficiency virus. Details on the synthesis of the TAT conjugate are found in Appendix E2 (supplement).…”
mentioning
confidence: 99%
“…Oximetry Response to CAR T-cell Therapy against Glioma by 19 F MRI: A Murine Model An alternative PFC nanoemulsion formulation displayed a cell-penetrating peptide as a component of the surfactant to boost cell labeling in T cells and other weakly phagocytic cell types (21), namely, the transactivating transcription sequence (TAT) of the human immunodeficiency virus. Details on the synthesis of the TAT conjugate are found in Appendix E2 (supplement).…”
mentioning
confidence: 99%
“…19 F may not be suitable for tracking labeled cancer cells to metastatic sites. Further improvements to PFPE nanoemulsions will enhance 19 F cellular sensitivity, such as incorporation of paramagnetic agents 16,17 , or the addition of surface modifications to enhance the uptake of PFPE nanoemulsions 18 .…”
Section: Discussionmentioning
confidence: 99%
“…To explore the biodistribution of cells, CPPs had also been used to help label and track CAR-T cells. In experiments on mice, TAT increased the MRI signal intensity of perfluorocarbon nano-emulsions by 8 times, and the tumor cell killing analysis showed that the markers did not affect cell function and viability [ 92 ]. Unfortunately, the application of CPPs to enhance MRI labeling effect of MSCs is still in the early experiments in vitro, although CPPs have been proven to be widely effective in increasing the signal strength of magnetic particles.…”
Section: Applications Of Cpps In Stem Cell Trackingmentioning
confidence: 99%